Developing entrepreneurial leadership styles in improving SMIs manufacturing Bumiputera technopreneurs performance in Melaka - Raja Abd Rahman, Raja Roslan; Din, Abdul Talib; Jamaludin, Azahari; Yusof, Tajuldin (Academy of Taiwan Business Management Review, 2010)
Understanding developing the effectiveness entrepreneurial leadership styles were important for theoretical and practical reasons because Bumiputera technopreneurial leaders were the individual that need to lead small and medium industries (SMIs) in today‟s innovative and dynamic market in Melaka. The objective of this study was to examine the developing effective entrepreneurial leadership styles in impoving SMIs manufacturing bumiputera technopreneurs performance in Melaka. The research had identified the certain personality traits, behaviors, competencies technopreneurial leaders. There were positive and significant relationship between entrepreneurial leadership styles namely transformational leadership style, transactional leadership style and charismatic style with entrepreneurial leaders‟ personality traits, entrepreneurial leaders‟ behaviours, entrepreneurial leaders‟ competencies, entrepreneurial leaders‟ monitoring companies‟ operation and entrepreneurial leaders‟ monitoring companies‟ performance. The analysis shown that Bumiputera technopreneurial leaders and entrepreneurial leaders‟ monitoring operation and performance among the Bumiputera can use it‟s to evaluate SMIs success and ventures success. Also practitioners of high-risk lending may be interested in methods of assessing entrepreneurial leadership that can be introduced into their risk calculus and potentially improve the likelihood of higher returns of their venture in investments. Thus, charismatic leadership style was found most highly related to entrepreneurial leaders‟ personality traits, entrepreneurial leaders‟ behaviours, entrepreneurial leaders‟ competencies, entrepreneurial leaders‟ monitoring companies‟ operation and entrepreneurial leaders‟ monitoring companies‟ performance followed by transactional leadership style and transformational leadership style. The conclusion, the research had provide insights for team building in executives‟ teams of SMIs, for example providing guidance in finding team members that can make unique contributions via their personality traits, behaviors, competencies and ways to monitor SMIs operation and performance. Suggestions of the research can be used as a guide to present and future SMIs technopreneurs regarding developing the effectiveness entrepreneurial leadership style that have to be practiced to become successful Bumiputera technopreneurial leader in Melaka.